The Management of Subject Teacher Forum (MGMP) at The Junior High School Level in Seri Amal Foundation - Paian Tamba; Yuniarto Mudjisusatyo (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
The purpose of this study was to determine the management of subject teacher forum (Musyawarah Guru Mata Pelajaran-MGMP) at junior high school level in Seri Amal Foundation. This study used the qualitative research method that derived descriptive data in the form of written or oral from the people. The source of data of researchers are the teachers and the Quality Assurance Council (Lembaga Penjamin Mutu-LPM) Seri Amal Foundation. The data were collected by interview. The results indicated that: (1) The MGMP planning in Seri Amal Foundation in the ever-new academic year by the Quality Assurance Council (LPM) of Seri Amal Foundation. Every MGMP in planning the preparation of learning materials and exam questions using whatsapp group and zoom meeting/google meet. (2) The implementation of the MGMP at the Seri Amal Foundation in the preparation of learning materials and exam questions is coordinated by the Head of the MGMP subject. (3) The MGMP evaluation is carried out after submitting learning materials and exam questions in the LPM Seri Amal Foundation’s email. Correction of learning materials and exam questions prepared by MGMP was carried out by LPM Seri Amal Foundation. The problem of late submission of learning materials and exam questions was handled by the head of the LPM and the Management of the Seri Amal Foundation by giving a warning or coaching to the MGMP through a zoom meeting.